2015
DOI: 10.1016/j.biocel.2015.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Glyceraldehyde-3-phosphate dehydrogenase is required for efficient repair of cytotoxic DNA lesions in Escherichia coli

Abstract: Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) is a multifunctional protein with diverse biological functions in human cells. In bacteria, moonlighting GAPDH functions have only been described for the secreted protein in pathogens or probiotics. At the intracellular level, we previously reported the interaction of Escherichia coli GAPDH with phosphoglycolate phosphatase, a protein involved in the metabolism of the DNA repair product 2-phosphoglycolate, thus suggesting a putative role of GAPDH in DNA repair p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 46 publications
(17 reference statements)
1
10
0
Order By: Relevance
“…These so-called moonlighting roles are associated with GAPDH's unusual, non-predictable localization. Such multifunctionality also has been reported for bacterial GAPDH in a number of independent studies (Pancholi and Fischetti, 1992;Modun and Williams, 1999;Boël et al, 2005;Butland et al, 2005;Arifuzzaman et al, 2006;Jin et al, 2011;Ferreira et al, 2015). In some human pathogens, the surface-localized and/or -secreted GAPDH is able to bind to several host proteins (Kopeckova et al, 2020), thus contributing to its virulence.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…These so-called moonlighting roles are associated with GAPDH's unusual, non-predictable localization. Such multifunctionality also has been reported for bacterial GAPDH in a number of independent studies (Pancholi and Fischetti, 1992;Modun and Williams, 1999;Boël et al, 2005;Butland et al, 2005;Arifuzzaman et al, 2006;Jin et al, 2011;Ferreira et al, 2015). In some human pathogens, the surface-localized and/or -secreted GAPDH is able to bind to several host proteins (Kopeckova et al, 2020), thus contributing to its virulence.…”
Section: Introductionsupporting
confidence: 64%
“…The results of a transcriptomic analysis on Streptococcus pyogenes mutant strain displaying higher intracellular levels of GAPDH suggest it has a role in transcriptional modulation of virulence and metabolic genes ( Boël et al, 2005 ). Several large-scale protein–protein interaction studies performed on Escherichia coli have revealed that bacterial GAPDH, similar to its eukaryotic orthologs or analogs, is able to interact with other intracellular proteins, including metabolic enzymes as well as proteins involved in transcription, protein synthesis, and DNA repair ( Butland et al, 2005 ; Arifuzzaman et al, 2006 ; Ferreira et al, 2013 , 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…It plays a fundamental role in energy metabolism and the generation of ATP along with pyruvate during glycolysis. It is also involved in DNA repair, DNA replication, transcription activation, and cell death . GAPDH has a number of cysteine residues that can be easily modified by fumarate leading to change in function of the enzyme .…”
Section: Main Cellular Targets Relevant To Its Clinical (Anti‐inflammmentioning
confidence: 99%
“…For further verification and functional analyses, Ferreira et al (2013) selected phosphoglycolate phosphatase (Gph), an enzyme involved in DNA repair of 3 ′ -phosphoglycolate ends caused by oxidative stress mediated by the radiomimetic agent bleomycin (Povirk, 1996;Pellicer et al, 2003). Further observations have pointed to a role of bacterial DNA repair machinery also in E. coli (Ferreira et al, 2015). GAPDH was shown to interact with other repair enzymes AP-endonuclease Endo IV and uracil DNA glycosylase.…”
Section: Interactions With Intracellular Bacterial Proteinsmentioning
confidence: 99%